Experimental Study on Repairing and Strengthening Seismically Damaged RC Frames by Installing H-Shaped Steel - Yuebing Li; Qushenglin Song; Hang Wang; Liang Shan; Dawei Liu; Shuang Xing (International Journal of Concrete Structures and Materials)
Abstract Seismic disaster investigations worldwide have revealed that a large number of reinforced concrete (RC) frame structures have been damaged or even collapsed. However, most of these buildings exhibit minor or moderate damage and can be repaired and strengthened. “Strong columns and weak beams, strong joints and weak components” is the concept of seismic design of buildings, and the failure of beam–column joints and columns is considered nonideal. For RC frame structures with damaged joints and columns, a method for repairing and strengthening damaged frames by installing H-shaped steel and pouring grout is proposed. By applying a pseudo static load, a frame structure specimen was damaged to simulate earthquake damage. After removing the crushed concrete, the damaged frame was repaired by pouring grout. Then, the structure was further strengthened by installing H-shaped steel on the columns using post-installed anchors. Through loading tests, seismic indices such as strength, deformation capacity, energy dissipation and failure mode of the frame before and after strengthening were compared. The results showed that the seismic performance of the repaired and strengthened frames exceeded that of the original frame, and the failure mode of the frame changed from joint shear and column-end bending to ideal beam-end yielding. Installing H-shaped steel and pouring grout could effectively strengthen the damaged frame, which provides a solution for repairing and upgrading damaged RC framed structures with a nonideal failure mode.